Catalytic hydrothermal conversion of algal residue to bio-bitumen. (1st November 2021) - Cardenas Velandia, Laura Carolina; Fontaine, Anne Elisabeth; Loquet, Denis; Checa, Ruben; Lorentz, Chantal; Bujoli, Bruno; Guilhaume, Nolven; Geantet, Christophe; Chailleux, Emmanuel; Queffélec, Clémence; Laurenti, Dorothée
Abstract: After extraction of high-added value components of Spirulina sp., the remaining residues can be valorized by hydrothermal liquefaction to produce an oily water insoluble viscous phase (biocrude) which is very similar to petroleum bitumen. This hydrophobic fraction is composed of various N-, O-containing cyclic compounds, fatty acids, amides, nitriles, alkenes and alkanes. In order to optimize the rheological properties of the biocrude, we studied the addition of different catalysts with various loadings: ZrO2 or CeO2, or Ce(NO3 )3 .6H2 O as well as the effect of residence time during HTL. The biocrude has been systematically characterized by GCxGC, GPC, elemental analyses and dynamic shear rheology and compared to a petroleum bitumen. The different catalysts tested had little influence on the composition of the HTL hydrophobic fraction in the chosen operating conditions. In contrast, increasing the reaction time (from 1 to 7 h) was found to promote condensation reactions, thereby increasing the average molecular weight of the biocrude, leading to a viscoelastic material very similar to a petroleum bitumen. Highlights: 1. Valorization of microalgae residues by catalytic HTL 2. Various catalytic system were compared (homogeneous and heterogeneous) 3. GPC, GCxGC-MS, elemental analysis were carried out on the biocrude 4. Bio-binder similar to petroleum one assessed by rheological characterization 5. Bio-bitumen rheology is strongly affected by the time of HTL